Innovating in a Learning Community Emergence of an Open Information Infrastructure in China's Pharmaceutical Distribution Industry - Reimers, Kai (Springer eBooks, 2014)
How do firms jointly develop open information infrastructures? To answer this question, this book draws on the results of a longitudinal research project covering the development of the pharmaceutical distribution industry in China from 2004 to 2012, focusing on the emergence and subsequent evolution of industry-wide information infrastructures. How do firms delimit areas of proprietary innovation in open innovation projects? How do firms coordinate, initiate, negotiate and implement the development of innovative infrastructures? How do processes and practices within firms enable and constrain such collective efforts? - This book provides answers to these questions and draws conclusions regarding the challenges and new capabilities that firms will need in a world in which participation in the building of open information infrastructures becomes a necessary task for commercial organizations.